Marriage Migrants of Japanese Women in Australia Remoulding Gendered Selves in Suburban Community - Hamano, Takeshi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book investigates the experience of Japanese women who have immigrated to Australia through marriage to a local partner. Based on long-term participant observations gathered with a Japanese ethnic association in Sydney, and on in-depth interviews with the association's members, it examines the ways in which the women remould themselves in Australia by constructing gendered selves that reflect their unique migratory circumstances through cross-border marriage. In turn, the book argues that the women tend to embrace expressions of Japanese femininity that they once viewed negatively, and that this is due to their lack of social skills and access to the cultural capital of mainstream Australian society. Re-molding the self through conventional Japanese notions of gender ironically provides them with a convincing identity: that of minority migrant women. Nevertheless, by analyzing these women's engagement with a Japanese ethnic association in a suburb of Sydney, the book also reveals a nuanced sense of ambivalence; a tension between the women's Japanese community and their lives in Australia. Accordingly, the book provides a fresh perspective on interdisciplinary issues of gender and migration in a globalized world, and engages with a wide range of academic disciplines including: sociology of migration; sociology of culture; cultural anthropology; cultural studies; Japanese studies; Asian studies; gender studies; family studies; migration studies and qualitative methodologies.
Acknowledgement -- 1. Japanese Women and International Marriage Migration -- 2. Japanese Emigration to Australia, 1880s-2000s -- 3. Nikkei' identity in Question: A Story of National Ethnic Japanese Organization in Australia between 1990 and 2000s -- 4. Relational Femininities: Exploring the Discourse of High Flexibility of Japanese Women's Gendered Selves -- 5. Becoming a Local Woman: The Logic of Ethno-Gendered Selves of Japanese Women in Greater Sydney -- 6. Bridging to the Mainstream: the Making of Group of Japanese Mothers in the Multicultural Community -- 7. Things Constructed through the Field work -- Appendix -- Bibliography -- Index.
Keywords: Culture; Emigration and immigration; Sex; Culture -- Study and teaching; Anthropology; Sociology of Culture; Human Migration; Gender Studies; Cultural Studies; Anthropology